Adverse events in rheumatoid arthritis patients under antimalarial treatment—Is there cardiovascular compromise? - Pedro Santos-Moreno; Linda Ibatá; Susan Martínez; Gabriel-Santiago Rodríguez-Vargas; Laura Villarreal; Pedro Rodríguez; Wilberto Rivero; Fernando Rodríguez-Florido; Adriana Rojas-Villarraga (Frontiers in Drug Safety and Regulation)
Introduction: The antimalarials chloroquine and hydroxychloroquine have been used for several decades in treating malaria and some autoimmune diseases—mainly rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE)—with excellent efficacy and safety. Due to the massive use of antimalarials worldwide for managing SARS-CoV-2/COVID-19 infection during the last 2 years and the consequent increase in cardiac arrhythmia, fear has risen about the safety of using antimalarials, especially for patients with increased cardiovascular risk.Objective: To describe a real-life experience about the safety of antimalarials in the setting of a single rheumatological center in Colombia.Methods: This is a cross sectional study that includes patients diagnosed with RA and treated with antimalarials between 2020 and 2021. Clinical follow-up information was gathered from the medical records, and all reported adverse events were described.Results: A total of 957 patients were included, primarily women (79.2%). The most frequent comorbidities were hypertension and osteoporosis. Chloroquine use was more frequent than hydroxychloroquine (86.4% vs. 13.6%). During the observation period, 243 (25.4%) patients presented at least one adverse event, 72 (29.6%) had retinal toxicity, 85 (35%) dermatological events, and 81 (33.3%) gastrointestinal intolerance. Other adverse events reported less frequently (15.2%) included headache, dizziness, lipothymia, and elevated transaminases. There were no reports of cardiovascular events from the period of antimalarial use to the date of data collection despite the high frequency of previous metabolic or cardiovascular disease in this cohort.Conclusion: This study reasserts the evidence of antimalarials safety profile for patients with rheumatological conditions such as RA. RA patients that were treated with antimalarials at doses recommended by the guidelines had no cardiovascular events.